2021
DOI: 10.1080/26410397.2021.1881206
|View full text |Cite
|
Sign up to set email alerts
|

Integrating human rights into sexual and reproductive health research: moving beyond the rhetoric, what will it take to get us there?

Abstract: The integration of human rights principles in sexual and reproductive health (SRH) research is often recognised to be of value. Good examples abound but lack of clarity persists as to what defines rights-inclusive SRH research. To help move the field forward, this article seeks to explore how key stakeholders responsible for funding and supporting rights in SRH research understand the strengths and weaknesses of what is being done and where, and begins to catalogue potential tools and actions for the future. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Unwanted teenage pregnancy has increased though it will take time for the epidemiological picture regarding teenage pregnancies to become clear [47]. It is likely that this increase will be highest in LICs/LMICs where access to sexuality education is poor and access to sexual and reproductive health services is limited by sociocultural and political factors [48,49]. Our study observed higher odds of increased sexual activities in LICs/LMICs when compared with HICs and higher odds of increased sexual activities for females.…”
Section: Plos Onementioning
confidence: 54%
“…Unwanted teenage pregnancy has increased though it will take time for the epidemiological picture regarding teenage pregnancies to become clear [47]. It is likely that this increase will be highest in LICs/LMICs where access to sexuality education is poor and access to sexual and reproductive health services is limited by sociocultural and political factors [48,49]. Our study observed higher odds of increased sexual activities in LICs/LMICs when compared with HICs and higher odds of increased sexual activities for females.…”
Section: Plos Onementioning
confidence: 54%
“…At SRHM, we would like to see change for the better and feel we can play a role in closing the gaps, strengthening the amalgamation of public health and rights-based frameworks, to advance the progress of rightsbased evidence for sexual and reproductive health. The article we published this year by Gruskin and colleagues 13 and reproductive health research. As part of our "more than a journal" activities, we are also working in partnership to improve approaches for how rights-based research is conducted (see http:// www.srhm.org/south-asia-regional-hub/).…”
Section: Challenge and Change Reflections From The Outgoing Editor-in-chiefmentioning
confidence: 99%